2018
DOI: 10.1039/c8ta02505c
|View full text |Cite
|
Sign up to set email alerts
|

Flexible carbon dots composite paper for electricity generation from water vapor absorption

Abstract: A scalable fabrication method for flexible moisture-electric energy transformation devices by dispersing or printing carbon dots on paper is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The close relationship between humidity and charge transfer resistance reflects affinity of water molecules onto the electrode surface, particularly docking of the adsorbed water molecules upon the polar residues (primarily OH and COOH units) on the C-dots’ surface [ 46 , 47 ]. As such, higher concentrations of physically adsorbed water molecules upon the C-dot-IDE surface would give rise to smaller Rct due to the conductive nature of water molecules [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The close relationship between humidity and charge transfer resistance reflects affinity of water molecules onto the electrode surface, particularly docking of the adsorbed water molecules upon the polar residues (primarily OH and COOH units) on the C-dots’ surface [ 46 , 47 ]. As such, higher concentrations of physically adsorbed water molecules upon the C-dot-IDE surface would give rise to smaller Rct due to the conductive nature of water molecules [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that commercial printing paper, pure cellulose films, and filler-free filter paper have abundant polarized oxygen groups that can release free protons allowing them to be used to generate electricity in moist conditions. [95,164] These MEGs are based on the ionic diffusion gradient mechanism, but the gradient in ion concentration and the electric field readily collapse, yielding transient voltage pulses when exposed to moisture (Figure 12). It is relevant that paper incorporating power generation units can also be assembled into various shapes and structures such as books, origami, and Chinese traditional paper fans (Figure 12a), with capabilities of harvesting energy from ambient moisture.…”
Section: Biofiber-based Megs For Transient Electricity Outputmentioning
confidence: 99%
“…For instance, graphene, various carbons, polymers, and biomolecules have all been demonstrated as potential electrokinetic converting materials for nano-hydroelectrics. 13,18,19 This ubiquity in materials selection provides a greater freedom for designing nano-hydroelectrics to target specific design requirements. Moreover, recent developments have made it possible to harvest energy from the vapor state as well, greatly expanding the versatility of nano-hydroelectrics.…”
Section: Introductionmentioning
confidence: 99%